Non-suicidal self-injury and its risk factors among Iranian high school and university students - Abbas Abbasi-Ghahramanloo; Behnam Khodadoust; Davoud Adham; Ali Gholami; Ali Gholami; Roya Farokhi; Vahid Maghsodlou-Nejad; Sima Afrashteh (Frontiers in Psychiatry)
BackgroundNon-suicidal self-injury (NSSI) is an important health problem among adolescents and young adults. The aims of this study were to determine NNSI status and its associated factors among students.MethodThis cross-sectional study has been conducted in 4715 high school and university students from the West and Northwest provinces of Iran. Multi-stage sampling was used to select students and all students completed survey questionnaires. Data analysis was performed using chi-square, Fisher’s exact test, binary and logistic regression.ResultThe lifetime prevalence of NSSI was estimated as 24.4% among all participants (21.4% in high school students vs. 29.3% in university students). After adjustment for other factors, age (OR=1.08,95%CI:1.03-1.12), cigarette smoking as an experimenter (OR=1.94,95%CI:1.61-2.34) and regular (OR=3.80,95%CI:2.96-4.89) compared to nonsmokers, membership in a sport team (OR = 1.26,95%CI:1.08-1.48), having physical fight (OR = 2.18,95%CI:1.85-2.57), doing general risk taking behavior (OR = 2.05,95%CI:1.66-2.53), and self-esteem (OR=0.93,95%CI:0.92-0.95) were associated with experience of NSSI.ConclusionOur results suggested that the prevalence of NSSI was relatively high among high school and university students. To diagnose, prevent, and treat NSSI in teenagers and young adults in Iran, more research is needed to identify the root causes.